30-Days to 10-Years Mortality Rates following Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of the Last Decade (2011–2021) - Pan, Xuankang; Turan, Oguz; Rullan, Pedro J.; Simmons, Hannah; Emara, Ahmed K.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2022)
Mortality data following primary total knee arthroplasty (TKA) beyond 1-year postoperative time period is sparse. This systematic review and meta-analysis aimed to: (1) estimate contemporary mortality rates at 30 days, 90 days, 1 year, 5 years, and 10 years following primary TKA; and (2) identify risk factors and causes of mortality following TKA. PubMed, MEDLINE, Cochrane, EBSCO host, and Google Scholar databases were queried from January 1, 2011 to October 30, 2021 for all studies reporting mortality rates following primary TKA. A meta-analysis of proportions was conducted using a random-effects model to ascertain pooled mortality rates (95% confidence interval [CI]). Meta-regression was utilized to account for confounding effects on mortality rates due to the study's country of origin, median date of study data, average patient age, and patient gender ratios, with a level of significance maintained at p-value <0.05. A total of 44 articles were included in quantitative synthesis. The pooled 30-day mortality rate was 0.14% (95% CI:0.05–0.22%; n = 1,817,647). The pooled 90-day mortality rate was 0.35% (95% CI:0.0.28–0.43%; n = 1,641,974). The pooled 1-year mortality rate was 1.1% (95% CI:0.71–1.49%; n = 1,178,698). The pooled 5-year mortality rate was 5.38% (95% CI:4.35–6.42%; n = 597,041). The pooled 10-year mortality rate was 10.18% (95% CI:7.78–12.64%; n = 815,901). Our 30-day mortality rate was lower than previously reported. The most common causes of death at all time points were due to cardiac disease, cerebrovascular disease, and malignancy. Obesity demonstrated mixed effects on long-term mortality rates. Overall mortality rates of TKA remain low worldwide at all time points and immediate postoperative mortality rates continue to fall. Compared to symptomatic knee osteoarthritic patients reported in the literature, TKA patients qualitatively exhibited lower mortality rates, which may support the value of TKA in improving quality of life without associated excess mortality. Future long-term mortality studies should be conducted to account for geographical variability in mortality rates and further elucidate modifiable risk factors associated with mortality among TKA patients.
Keywords: total knee arthroplasty; osteoarthritis; mortality; outcome; knee